Understanding smart home automation acceptance through users’ lifestyles and perceived difficulty of use: Evidence from South Korea - Young-Gwan Kim; Do-Hyeon Ryu; Kwang-Jae Kim (PLoS ONE, 2026)
Smart home automation (SHA) is an advanced service that automates household tasks with minimal human intervention, enhancing efficiency, convenience, and personalization. SHA serves as the critical bridge that transforms home environments into intelligent spaces that respond adaptively to user needs. Despite these benefits, SHA penetration remains limited due to various challenges, making it essential to understand SHA acceptance. This study examines two user-centered constructs influencing SHA acceptance: users’ lifestyles (UL) and perceived difficulty of use (PDU). Through a systematic process, the dimensions of both constructs were defined and measurement items were developed. A research model extending the Technology Acceptance Model was proposed, in which UL and PDU influence the perceived usefulness (PU) and intention to use (IU) of SHA. The model was tested using data collected from 167 non-users of SHA in South Korea. Results reveal that UL characterized by energy-saving negatively affects IU, whereas UL characterized by lack of time for household tasks positively affects IU. Additionally, PDU from automation configuration negatively affects both PU and IU. Based on these findings, practical strategies to enhance SHA acceptance are proposed. This study contributes by extending the acceptance framework for SHA through conceptualizing UL and PDU and by revealing how these user-centered constructs shape PU and IU, thereby clarifying their role in SHA acceptance and informing managerial strategies that promote broader penetration.